2021
DOI: 10.1002/app.51346
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixed soft segment on the microstructure of thermoplastic polyurethane

Abstract: In this work, we fixed the hard segment content (Ch%) and synthesized thermoplastic polyurethane (TPU) elastomers with one‐soft segment (HTPB‐PU, PTMG‐PU, and PCL‐PU) and bi‐soft segment (PTMG‐HPU and PCL‐HPU), using 4,4′‐diphenylmethane diisocyanate, 1,4‐butanediol, and different oligomer diols as raw materials. This work was used to explore the impact of two polar diols (polytetrahydrofuran diol [PTMG]; polycaprolactone diol [PCL]) of the hydroxy‐terminated polybutadiene (HTPB)‐based TPU on the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In this study, ATR-IR spectroscopy and DSC were mainly used for assessing the degree of micro-phase separation and miscibility of the TPUs synthesized with PPG+PAd mixed SS. Several previous studies [19][20][21][22][23][24][25] have demonstrated that the degree of microphase separation of the TPUs can be assessed by using these experimental techniques. The…”
Section: Tpus and Tpu Psas Synthesized With Ppg+pad Mixed Soft Segments By Using An Nco/oh Ratio Of 130mentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, ATR-IR spectroscopy and DSC were mainly used for assessing the degree of micro-phase separation and miscibility of the TPUs synthesized with PPG+PAd mixed SS. Several previous studies [19][20][21][22][23][24][25] have demonstrated that the degree of microphase separation of the TPUs can be assessed by using these experimental techniques. The…”
Section: Tpus and Tpu Psas Synthesized With Ppg+pad Mixed Soft Segments By Using An Nco/oh Ratio Of 130mentioning
confidence: 99%
“…In this study, ATR-IR spectroscopy and DSC were mainly used for assessing the degree of micro-phase separation and miscibility of the TPUs synthesized with PPG+PAd mixed SS. Several previous studies [19][20][21][22][23][24][25] have demonstrated that the degree of microphase separation of the TPUs can be assessed by using these experimental techniques. The ATR-IR spectrum of 1.30/PPG in Figure 3 shows the bands of the urethane HS at 3303 cm −1 (N-H stretching), 1728 cm −1 (C=O stretching), 1598 cm −1 (benzene ring of MDI) and 1535 cm −1 (N-H bending), and the ones of the PPG SS appear at 2941 and 2867 cm −1 (asymmetric and symmetric C-H stretching respectively) and 1091 cm −1 (C-O stretching of ether).…”
Section: Tpus and Tpu Psas Synthesized With Ppg+pad Mixed Soft Segments By Using An Nco/oh Ratio Of 130mentioning
confidence: 99%
See 3 more Smart Citations